2011
DOI: 10.1007/s10499-011-9447-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid levels on growth, nutrient utilization, and nitrogen and carbon balances in shi drum (Umbrina cirrosa L.)

Abstract: Shi drum (Umbrina cirrosa L.) is regarded as a promising new candidate for Mediterranean mariculture but specifically formulated feeds are not yet available due to knowledge gaps in its basic nutritional requirements. Therefore, this study was carried out to determine the effects of dietary lipid levels on growth and feed utilization in shi drum (72.6 g average weight). Four isonitrogenic diets differing in dietary lipid levels between 10 and 19% (named 10L, 13L, 16L, and 19L, respectively) were fed to triplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Concerning dietary lipid levels, our study also showed that lipid significantly deteriorated growth, feed and protein utilization in levels >100g/kg in the diets, as it was previously suggested (Akpınar, Sevgili, Demir, et al, ). Overall, some studies attribute the reduced growth of fish fed on high dietary lipid levels to the excessive energy which can affect feed intake or to the limited ability of the animals to digest and absorb high lipid concentrations (Lupatsch, Kissil, Sklan, & Pfeffer, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Concerning dietary lipid levels, our study also showed that lipid significantly deteriorated growth, feed and protein utilization in levels >100g/kg in the diets, as it was previously suggested (Akpınar, Sevgili, Demir, et al, ). Overall, some studies attribute the reduced growth of fish fed on high dietary lipid levels to the excessive energy which can affect feed intake or to the limited ability of the animals to digest and absorb high lipid concentrations (Lupatsch, Kissil, Sklan, & Pfeffer, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Although limited studies exist on the dietary requirements of the shi drum, this species seems to have high dietary protein requirements, while it has a limited ability to use lipid as a primary energy source. Two previous studies from Akpınar, Sevgili, Demir, et al () and Akpinar, Sevgili, Özgen, et al () recommended that juvenile shi drum weighing 70–80 g should have dietary protein levels ranging from 470 to 530g/kg in order to achieve optimal growth and feed utilization. Moreover, these studies also suggested that dietary lipids should not exceed 130g/kg levels of inclusion, as it was shown to cause deteriorated performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across a wide taxonomic spectrum, vertebrate animals faced with food restriction preferentially mobilize glycogen and lipid stores for energy production (Wang et al 2006), thereby increasing the C:N ratio of their metabolism, reducing amino acid catabolism, and lowering the production of N waste as NH 3 (Sinha et al 2012;Liew et al 2013). The adaptive significance of these changes is a sparing of the resource stores (i.e., protein) most needed for future physiological activities (McCue 2010), thereby increasing the efficiency of N retention (Kousoulaki et al 2010;Akpınar et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited information about nutrition of this carnivorous fish is available. The existing information is related to the potential use of vegetable protein and oil sources in its diets (Segato et al, 2005a), dietary lipid to nitrogenous-free extract ratio (Segato et al, 2005b), dietary protein (Akpιnar et al, 2012) and lipid requirements (Akpınar et al, 2012) and optimal dietary protein/lipid ratio (Henry and Fountoulaki, 2014). These studies suggest that juvenile shi drum requires high protein (47-50%) and relatively low lipid (<13%).…”
Section: Introductionmentioning
confidence: 99%